Realism and Virtues in Ottoman Political Thought - Erol Fırtın (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
This article presents a novel perspective, arguing for a virtue-based weak version of political realism in Ottoman political thought (OPT). By recognizing realist elements in human nature and poli- tics in OPT tradition, we can gain a deeper understanding of the place of morality in politics. Challeng- ing the common sense understanding of morality that pervades all areas of politics, this paper provides compelling evidence to show how the understanding of the nature of politics in OPT was ever-chang- ing, singular, and, to a certain extent, free of morality. This unique framing of politics and human na- ture in the OPT tradition makes it a realist one. Finally, I delve into the role of universals in explaining the intricate relationship between politics and morality through various analytical distinctions.